Antibiotic Exposure, Common Morbidities and Main Intestinal Microbial Groups in Very Preterm Neonates: A Pilot Study - Nicole Bozzi Cionci; Laura Lucaccioni; Elisa Pietrella; Monica Ficara; Caterina Spada; Paola Torelli; Luca Bedetti; Licia Lugli; Diana Di Gioia; Alberto Berardi (Antibiotics, 2022)
Prematurity exposes newborns to increased risks of infections and it is associated with critical morbidities. Preterm infants often require antibiotic therapies that can affect the correct establishment of gut microbiota. The aim of this study was to investigate targeted intestinal bacteria in preterm neonates with common morbidities and receiving antibiotic treatments of variable duration. Stool samples were collected after birth, at 15, 30 and 90 days of life. qPCR quantification of selected microbial groups (Bifidobacterium spp., Bacteroides fragilis group, Enterobacteriaceae, Clostridium cluster I and total bacteria) was performed and correlation between their levels, the duration of antibiotic treatment and different clinical conditions was studied. An increasing trend over time was observed for all microbial groups, especially for Bifdobacterium spp. Prolonged exposure to antibiotics in the first weeks of life affected Clostridium and B. fragilis levels, but these changes no longer persisted at 90 days of life. Variations of bacterial counts were associated with the length of hospital stay, feeding and mechanical ventilation. Late-onset sepsis and patent ductus arteriosus reduced the counts of Bifidobacterium, whereas B. fragilis was influenced by compromised respiratory conditions. This study can be a start point for the identification of microbial biomarkers associated with some common morbidities and tailored strategies for a healthy microbial development.